PENINGKATAN KETERAMPILAN MENULIS NASKAH DRAMA MELALUI KOLABORASI MEDIA GAMBAR SERI DAN KERJA KELOMPOK PADA SISWA KELAS VIII A SMP NEGERI 2 KALINYAMATAN JEPARA TAHUN AJARAN 2010/2011 - TEGUH, TEGUH (2011)
The objectives of this study are to describe :1) Is the colaboration media picture series and work group increase the students skill on writing drama script, 2) is there increasing on seriousness and being active , and 3) is there increasing preception and response of the students at class VIII A SMP Negeri 2 Kalinyamatan, Jepara, year 2010/2011 toward colaboration media picture series and work group in learning process on writing drama script. The study uses an action reserach. Subject of this study is the students class VIIIA SMP Negeri 2 Kalinyamatan, Jepara that amount forty two students. The data sources such as: 1) informant and 2) documen. Informant in this study is the students class VIII A and MH. Rozikiyah, S.Pd, as Indonesian`s teacher of class VIII A. Documen that used is the student`s score on writing drama script, student`s work, observation paper, interview result, and quesioner. The technique to collect the data such as: interview with the students, 2) observation, 3) quesioner, 4) test, and 5) docoment analysis. Validity test that used is: triangulasi methode, data source, and riview informant. The data analyzed with descriptive statistic technique and qualitative. Based on the result of the study can be presented that the application of picture series media and work gruop increase the writing skill on drama script, seriousness and being active, and preception and student`s response of student class VIII A SMP Negeri 2 Kalinyamatan, Jepara. This point reflects as follow: The quality learning process of writing drama script is increased. This point can be seen from: interest and motivation student is increased, the student`s attention focus on following learning proces on writing, the students become active during the lesson , presence the increasing skill quality on writing drama script.This point can be seen from students that success to reach the tudent`s standar for about 63,04 and 17 from 42 students that success reach the standar to passing a study. In the frist cyclus, the everage student score is 69,19 and 30 students success to pass the standard. In the second cyclus, the student everage score is 73,09 and 37 students succes to pass the standrad of the study.